CXCL16 regulates cisplatin-induced acute kidney injury - Liang, Hua (Oncotarget, 2016)
The pathogenesis of cisplatin-induced acute kidney injury (AKI) is characterized by tubular cell apoptosis and inflammation. However, the molecular mechanisms are not fully understood. We found that CXCL16 was induced in renal tubular epithelial cells in response to cisplatin-induced AKI. Therefore, we investigated whether CXCL16 played a role in cisplatin–induced tubular cell apoptosis and inflammation. Wild-type and CXCL16 knockout mice were administrated with vehicle or cisplatin at 20 mg/kg by intraperitoneal injection. CXCL16 knockout mice had lower blood urea nitrogen and less tubular damage following cisplatin-induced AKI as compared with wild-type mice. Genetic disruption of CXCL16 reduced tubular epithelial cell apoptosis and decreased caspase-3 activation. Furthermore, CXCL16 deficiency inhibited infiltration of macrophages and T cells into the kidneys following cisplatin treatment, which was associated with reduced expression of the proinflammatory cytokines in the kidneys. Taken together, our results indicate that CXCL16 plays a crucial role in the pathogenesis of cisplatin–induced AKI through regulation of apoptosis and inflammation and maybe a novel therapeutic target for cisplatin-induced AKI.